2017
DOI: 10.15761/cmi.1000132
|View full text |Cite
|
Sign up to set email alerts
|

Osteomyelitis: A manifestation of sickle cell anemia

Abstract: Osteomyelitis is an infectious stage of bones associated with distinct clinical microbiology. In sickle cell anemia, an early detection and diagnostic accuracy of osteomyelitis would establish an immediate treatment module for preventing bone destruction and deformity. This mini-review highlights the different diagnostic tools and courses of treatment involved in the accurate diagnosis of osteomyelitis.In approximately 50% of acute osteomyelitis cases, blood culture is considered as an essential tool for corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
0
7
0
3
Order By: Relevance
“…Untreated, chronic osteomyelitis can lead to severe bone damage, life-threatening infections and a decreased quality of life. 20 Due to the extensive mandibular involvement, surgical excision was not an ideal management option in both our cases requiring the need to consider alternatives.…”
Section: Discussionmentioning
confidence: 91%
“…Untreated, chronic osteomyelitis can lead to severe bone damage, life-threatening infections and a decreased quality of life. 20 Due to the extensive mandibular involvement, surgical excision was not an ideal management option in both our cases requiring the need to consider alternatives.…”
Section: Discussionmentioning
confidence: 91%
“…Due to this sickle shaped RBC they can manifest with multisystem complication like splenic sequestration, sickle cell pain (Dactylytis), osteomyelitis, avascular necrosis, priapism, stroke and acute chest syndrome. 5 Hepatobiliary complications of SCD are not well established in pediatric age group. Allali et al in their cohort retrospective study on 616 SCD pediatric patients reported 37% of the children developed one hepatobiliary complication.…”
Section: Discussionmentioning
confidence: 99%
“…Radiographic findings of osteopenia, sclerosis, and periosteal inflammation are seen in both stages of infection and infarction. Therefore, the radiographic features are nonspecific and primarily normal [4] [5]. We report the case of a three-year-old female sickle cell patient with chronic bone pain, which was later diagnosed as chronic osteomyelitis and cared for.…”
Section: Introductionmentioning
confidence: 97%
“…The infection is haematogenous in nature due to its delayed onset. Immunodeficiency caused by splenic dysfunction, tissue infarction, and excess iron content leads to an increased risk of osteomyelitis [4]. In SCA, osteomyelitis diagnosis can be a major problem for healthcare providers, where unsuccessful identification of the disease may end up with severe bone damage and progression of infection to life-threatening status.…”
Section: Introductionmentioning
confidence: 99%